Peran UMKM dalam Pertumbuhan Ekonomi Indonesia: Perspektif Teori Schumpeterian - Anita Br Saragih; Radhika Narwastu; Hasiandra Simanjuntak; Lokot Muda Harahap (Moneter : Jurnal Ekonomi dan Keuangan, 2025)
This study uses a qualitative method with a case study approach to analyze the contribution of MSMEs to Indonesia's economic growth. The results of the study indicate that MSMEs play an important role in accelerating economic growth through innovation and entrepreneurship, although there are still structural obstacles that hinder the development of this sector. Therefore, policies are needed that support access to capital, digitalization, and increasing the capacity and competitiveness of MSMEs so that they can survive and thrive in the era of globalization and digitalization.